2021
DOI: 10.3390/plants10010185
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present and Future of Cannabis sativa Tissue Culture

Abstract: The recent legalization of Cannabis sativa L. in many regions has revealed a need for effective propagation and biotechnologies for the species. Micropropagation affords researchers and producers methods to rapidly propagate insect-/disease-/virus-free clonal plants and store germplasm and forms the basis for other biotechnologies. Despite this need, research in the area is limited due to the long history of prohibitions and restrictions. Existing literature has multiple limitations: many publications use hemp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 150 publications
(305 reference statements)
2
76
0
Order By: Relevance
“…Micropropagation is the first and foremost application of in vitro culture in cannabis [ 10 , 47 , 60 , 61 ]. While micropropagation for applications in genetic preservation or propagation are generally achieved through shoot proliferation from existing meristems, many applications in biotechnology require the establishment of de novo regeneration in which plants are produced from non-meristematic tissues.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
See 1 more Smart Citation
“…Micropropagation is the first and foremost application of in vitro culture in cannabis [ 10 , 47 , 60 , 61 ]. While micropropagation for applications in genetic preservation or propagation are generally achieved through shoot proliferation from existing meristems, many applications in biotechnology require the establishment of de novo regeneration in which plants are produced from non-meristematic tissues.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…However, the optimal condition for in vitro propagation may not be optimal to preserve the genetic integrity of the regenerated genotype [ 151 ]. Indeed, in vitro conditions such as medium composition, PGRs, high humidity, the number of subcultures, length of the culture period, temperature, light quality, and light intensity can eventually result in several developmental and physiological aberrations of the micropropagated plants [ 60 ]. The term “somaclonal variation” refers to any phenotypic variation detected among micropropagated plants [ 151 ].…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…All leaf material was sourced from in vitro shoots maintained within a long-term in vitro germplasm at the University of Guelph. All explants used in this experiment were from Stage 2 in vitro grown shoots maintained as previously described [6,13]. The plants had been in a state of vegetative growth for at least 6 months and were routinely subcultured ever 4-6 weeks.…”
Section: Regeneration From Leaf-derived Explantsmentioning
confidence: 99%
“…In C. sativa, the majority of micropropagation studies rely on shoot multiplication from existing meristems found in the apical and axillary buds [6]. Numerous protocols report regeneration from meristematic tissues at levels greater than 70% [4,[7][8][9], with the most effective of these protocols rely on existing meristems found in the nodal tissues of vegetative cuttings.…”
Section: Introductionmentioning
confidence: 99%
“…BAP was essential factor for shoot proliferation, whereas poor shoot development occurred on the media without cytokinins. In fact, certain explants will be more responsive than the others for instance the cotyledon of some species regenerate shoot better than true leaves or stems [39,52].…”
Section: Effect Of Auxins and Cytokinins On Shoot Formation From Cotyledon Explantsmentioning
confidence: 99%